Analysis of Discretization Methods for Time Fractional Diffusion and Diffusion Wave Equations with Weak Initial Singularity - Kumari, Sarita (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Mathematical Sciences